Prognostic significance of MGMT & ERCC1 gene polymorphism in lung cancer patients treated with platinum-based doublet chemotherapy - Gupta, Anu (My University, 2018)
Lung cancer is the leading cause of death worldwide. Non-small cell lung cancer (NSCLC) contributes about 80-85 % of the lung cancer and rest is contributed by small cell lung cancer (SCLC). It has been reported that genetic variation in DNA repair genes may affect the chemotherapeutic response among non-small cell lung cancer patients. MGMT gene and ERCC1 gene plays an important role in DNA direct reversal pathway and Nucleotide Excision repair pathway respectively. Present study focuses on the chemotherapeutic response to platinum based drug in lung cancer patients of North India related to genetic variants of MGMT and ERCC1. It includes a total of 214 patients treated with platinum based chemotherapy (docetaxel, irinotecan or pemetrexed in combination with cisplatin/ carboplatin). Prognosis was observed for MGMT (rs12917) and ERCC1 (rs3212986) individually and in combination. PCR-RFLP methodology was used to classify the patients into wild type, heterozygous type and mutant type genotype. The genotypic distribution of MGMT and ERCC1 (individually as well as in combination) falls within Hardy-Weinberg equilibrium. Univariate analysis showed a non-significant association of genetic polymorphism in MGMT (rs12917) and ERCC1 (rs3212986) (when analysed individually and in combination) with overall survival on the basis of parameters like genotype, smoking status, pack per years, gender, regimen and histology. Also when analysed by logistic regression method, a non-significant relationship of genetic polymorphism in MGMT (rs12917) and ERCC1 (rs3212986) (when analysed individually and in combination) with the tumor stage, primary tumor extension, metastasis, lymph node involvement, ECOG, KPS and clinical response among lung cancer patients was also observed. Furthermore genetic polymorphism in MGMT (rs12917) and ERCC1 (rs3212986) (when analysed individually and in combination) was associated with heavy smokers and not associated with chemotherapeutic regimens. In-silico analysis showed that ERCC1 gene polymorphism present outside of protein domain and was tolerated in nature; while results were contradictory and inconsistent for MGMT that according to some analysis this was observed inside of protein domain and deleterious in nature whereas according to other software was present outside of protein domain and its effect was neutral in nature. In conclusion large sample sizes are needed to evaluate the effect of these polymorphism on overall survival.
Keywords: lung cancer; polymorphism; MGMT; ERCC1